Motivation of Non-Muslims to Become Customers at PT. Bank Syariah Mandiri KC. Sibolga - amsal amsal; fatahuddin siregar; idris saleh; ferri alfadri (Journal Of Sharia Banking, 2020)
The background of the problem in this study is PT. Bank Syariah Mandiri KC. Sibolga does not only have customers who are Muslim but PT Bank Syariah Mandiri KC. Sibolga has non-Muslim customers who account for almost half of the total customers who are motivated to make transactions at the bank. This shows that PT Bank Syariah Mandiri KC. Sibolga is well received by the non-Muslim community in the city of Sibolga. Discussion of research related to the field of Islamic banking. Islamic banks are financial institutions that encourage and invite the public to participate in various products based on sharia principles. While motivation is a set or collection of behaviors that provide a basis for a person to act in a way that is directed towards certain specific goals. The research method used is qualitative research using a descriptive approach. The types of data used are primary data sources and secondary data sources. Taknik followed the data with observation, interviews and documentation. Based on the results of the research conducted, researchers saw that in general the non-Muslim community was motivated by the services provided by PT. Bank Syariah Mandiri KC. Sibolga. motivation of the non-Muslim community to become customers at PT. Bank Syariah Mandiri KC. Sibolga's location is very affordable, a promotion conducted by PT. Bank Syariah Mandiri KC. Sibolga is very suitable with socializing in the market and at school. In addition there are also those who change because of the rules of the Ministry of Religion office that roam as customers at PT. Bank Syariah Mandiri KC. Sibolga.